One or many? The grammatical number of suffixed nouns as a text-critical problem - Krusche, Marcel 1989- (2023)
One of the most frequent cases of textual variance in the Hebrew Bible concerns the grammatical number of nouns with suffixes (e.g. ידך‎ ‘your hand’ versus ידיך‎ ‘your hands’). First, this article demonstrates the significant textual instability of the letter yod in the plural or dual morphemes of suffixed nouns and traces some reasons for that. Then, it presents exemplary cases of this variance and discusses some interpretive conclusions drawn from conspicuous grammatical numbers in the research literature. For instance, a widespread theory that distinguishes two kinds of hand imposition rites according to the number of hands used by the performing subject proves to be problematic for text-critical and philological reasons. Finally, the article discusses the appropriate text-critical handling of the problem in general, suggests some guidelines, promotes awareness of ambiguity, and pleads for restraint in drawing far-reaching interpretive conclusions from a specific grammatical number of suffixed nouns.
Keywords: Ambiguity; lectio difficilior; imposition of hands; spelling; letter yod; nouns with suffixes; grammatical number; Textual Criticism